The Relevance of Social Media Adoption for Public Organizations in Policy Making - Agung Budiono; Roy Valiant Salomo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The emergence of social media is a phenomenon in the digital world that’s relevant to be adopted appropriately by public organizations such as the government. The government's use of social media deliberately encourages improving good governance practices through e-government platforms, especially transparency and public participation. Moreover, data from social media can be helpful in the input of the policymaking process. On the other hand, social media is just a tool that provides features that allow users to interact in a two-way and real-time manner. However, testing the data requires further analysis to obtain causality between the intended use and the input data acquired to obtain expected results. By conducting a literature review method, this study reviews how public organizations can adopt social media to support the policymaking processes. In addition, this study also notes the potential gaps and risks in using social media for public organizations to make policies.